Pengaruh Kampanye Media Online ‘Kitabisa.Com’ Terhadap Minat Berdonasi - Meganing Laras Saputri; Nurtyasih Wibawanti Ratna Amina (LPPM Stikosa-AWS, 2022)
Kitabisa.com is a crowdfunding platform that is quite popular for raising funds in the form of a donation campaign since 2013 by raising the issue of social problems produced through Kitabisa to be distributed to the public to be used as a tool to get financial improvement. This research was conducted to measure how much influence the campaign on the Kitabisa.com website as a crowdfunding platform has on the interest in donating members of the Community, namely #OrangBaik Kitabisa.com. Selected 100 respondents who meet the criteria of researchers from 5000 members taken from the community. This study uses AIDDA theory which explains a psychological process that occurs in the communicant audience in receiving communication messages. The method in this study uses quantitative correlation by providing a questionnaire via google form. With data obtained through a questionnaire distributed to 100 respondents. The results of the study show that the campaign can influence so that the interest in donating is equal to 58.2 percent. So it can be said that Ho is rejected and Ha is accepted, meaning that there is a relationship or there is a significant influence between the Kitabisa.com campaign on interest in donating community members.